Cyclotrons Operated for Nuclear Medicine and Radiopharmacy in the German Speaking D-A-CH Countries: An Update on Current Status and Trends - Zippel, Claus; Ermert, Johannes; Patt, Marianne; Gildehaus, Franz Josef; Ross, Tobias L.; Reischl, Gerald; Kuwert, Torsten; Solbach, Christoph; Neumaier, Bernd; Kiss, Oliver; Mitterhauser, Markus; Wadsak, Wolfgang; et al. (Frontiers in Nuclear Medicine, 2022)
Background Cyclotrons form a central infrastructure and are a resource of medical radionuclides for the development of new radiotracers as well as the production and supply of clinically established radiopharmaceuticals for patient care in nuclear medicine. Aim To provide an updated overview of the number and characteristics of cyclotrons that are currently in use within radiopharmaceutical sciences and for the development of radiopharmaceuticals to be used for patient care in Nuclear Medicine in Germany (D), Austria (A) and Switzerland (CH). Methods Publicly available information on the cyclotron infrastructure was (i) consolidated and updated, (ii) supplemented by selective desktop research and, last but not least, (iii) validated by members of the committee of the academic “Working Group Radiochemistry and Radiopharmacy” (AGRR), consisting of radiochemists and radiopharmacists of the D-A-CH countries and belonging to the German Society of Nuclear Medicine (DGN), as well as the Radiopharmaceuticals Committee of the DGN. Results In total, 42 cyclotrons were identified that are currently being operated for medical radionuclide production for imaging and therapy in Nuclear Medicine clinics, 32 of them in Germany, 4 in Austria and 6 in Switzerland. Two thirds of the cyclotrons reported (67%) are operated by universities, university hospitals or research institutions close to a university hospital, less by/in cooperation with industrial partners (29%) or a non-academic clinic/ PET-center (5%). Most of the cyclotrons (88%) are running with up to 18 MeV proton beams, which is sufficient for the production of the currently most common cyclotron-based radionuclides for PET imaging. Discussion The data presented provide an academically-updated overview of the medical cyclotrons operated for the production of radiopharmaceuticals and their use in Nuclear Medicine in the D-A-CH countries. In this context, we discuss current developments and trends with a view to the cyclotron infrastructure in these countries, with a specific focus on organizational aspects.